2002
DOI: 10.1046/j.1439-0337.2002.00073.x
|View full text |Cite
|
Sign up to set email alerts
|

The Target Tree Management System. Die Z-Baum-Kontrollmethode

Abstract: Summary: The global need to increase sustained forestry value production requires an operational silviculture and a practical method for controlling tree growth, especially that of target trees. The target tree management system has been designed for this purpose. It is applicable as a decision support tool in stands of any size and structure, including pure and mixed stands.For controlling the growth of selected target trees, only a few tree parameters (age, height and diameter) need to be taken from sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 1 publication
0
22
0
1
Order By: Relevance
“…However, its labour consumption is high (Schütz 1987) because it operates on the basis of frequent care of an excessively high number of trees (ca 2,000 individuals) but only about 5% of them require such a care. This is the reason why its rational choice of canditates is focused only on vital straight trees, or implemented selection variant by Abetz (1974), Abetz and Klädtke (2002) in the form of target trees (Z-Bäu-men). It can be considered more reasonable but only if the prescriptive number (80-100 trees per ha) is increased to a double stock like recommendied Assmann (1961) for beeach stands.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its labour consumption is high (Schütz 1987) because it operates on the basis of frequent care of an excessively high number of trees (ca 2,000 individuals) but only about 5% of them require such a care. This is the reason why its rational choice of canditates is focused only on vital straight trees, or implemented selection variant by Abetz (1974), Abetz and Klädtke (2002) in the form of target trees (Z-Bäu-men). It can be considered more reasonable but only if the prescriptive number (80-100 trees per ha) is increased to a double stock like recommendied Assmann (1961) for beeach stands.…”
Section: Resultsmentioning
confidence: 99%
“…(4) Diameter increment and basal area increment were proportionate to crown width and horizontal projection; the thicker the tree, the larger the increment (Utschig, Pretzsch 2001;Lockow 2003;Reushler et al 1993). (5) In the stand with repeated quality selection and in the stand with target trees the number of high-quality trees at the age of 73 years is twice to three times higher than the number of target trees (90-100) recommended by Abetz and Klädtke (2002). (6) The selection of candidates and target trees at the small pole stage is a premature and risky practice because in spite of their initial high quality they may be deformed in the course of time (Kennel 1979;Richter 1979;Spellmann, Dies 1990;Assman 1961;Mosandl et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…However, inherent potential risks may hamper the achievement of those targets, in particular, in natural and semi-natural systems that are not under strict human control. Potential future crop trees are such a potential target in oak stands managed for high-value timber production (Abetz and Kladtke 2002). How many future crop trees per unit area are needed after the first commercial thinning, which commonly takes place in 35-to 50-year-old stands, is a matter of ongoing debate.…”
Section: Risks and Benefits Of Cluster Planting -An Outlookmentioning
confidence: 99%
“…A study on the development of potential future crop trees in oak stands established by row planting showed that 9%-14% of such trees either died (e.g., by pathogen attack or by wind and snow damage) or were downgraded in quality (e.g., epicormic sprouting) (Spellmann and von Diest 1990). However, a loss in future crop trees is sometimes seen as the result of flawed management decisions during early selection, promotion, and tending rather than a failure of the silvicultural system oriented towards future crop trees (Abetz 1980;Abetz and Ohnemus 1999).…”
Section: Risks and Benefits Of Cluster Planting -An Outlookmentioning
confidence: 99%
“…For example, research shows that late thinning of young dense stands increases the risk of snow damage, such as stem breakage (Valinger et al 1994;Päätalo et al 1999). Furthermore, stands of smaller diameter trees (diameter at breast height, DBH < 80 mm), which result from the thinning of young dense stands, are more susceptible to damage (Päätalo et al 1999;Abetz and Klädtke 2002). On the other hand, there is evidence that BT can precede a later harvest of crop trees without risking crop tree value (Ulvcrona 2011).…”
Section: Introductionmentioning
confidence: 99%